DETECTION OF CANINE PARVOVIRUS ANTIGEN IN DOGS IN KUMASI, GHANA - Folitse, R. D; Kodie, D.O; Amemor, E; Dei, D; W, Tasiame; Burimuah, V; Emikpe, B. O (African Journal of Infectious Diseases (AJID), 2017)
Background: Canine Parvovirus (CPV) in dogs has been documented in many countries. However, evidence of the infection is scanty in Ghana. This study was conducted to detect canine parvovirus antigen in dogs presented with diarrhoea to the Government Veterinary Clinic in Kumasi, Ghana. Materials and Methods: Faecal samples from 72 dogs presented with diarrhoea were tested for the presence of canine parvovirus antigen using commercially available rapid test kit (BIT® Rapid Colour Canine Parvovirus Ag Test Kit, BIOINDIST Co. Ltd, Korea) based on the principle of immunochromatography. Influence of breed, sex, age, vaccination history and the nature of diarrhoea were assessed. Data obtained was analysed with SPSS and subjected to the chi-square test. Significance was at α0.05 Results: We found 61.11% tested positive (44/72) for CPV. Based on sex, 61.54% of males (20/33) and 60.61% of females tested positive (24/39). A total of 65.67% of samples from puppies below 6 months were positive. 56.25% of CPV vaccinated dogs and 70.83% of unvaccinated dogs were positive respectively. 69.05% of samples from haemorrhagic diarrhoeic dogs and 50.00% from non-haemorrhagic diarrhoeic dogs were positive of CPV. Conclusion: The study is the first documented evidence of the existence of CPV in Ghana. It also revealed that absence of bloody diarrhoea does not necessarily rule out CPV infection.